Cerebral misery perfusion due to carotid occlusive disease - Maddula, Mohana; Sprigg, Nikola; Bath, Philip M.W.; Munshi, Sunil K. (BMJ, 2017)
Purpose Cerebral misery perfusion (CMP) is a condition where cerebral autoregulatory capacity is exhausted, and cerebral blood supply in insufficient to meet metabolic demand. We present an educational review of this important condition, which has a range of clinical manifestations. Method A non-systematic review of published literature was undertaken on CMP and major cerebral artery occlusive disease, using Pubmed and Sciencedirect. Findings Patients with CMP may present with strokes in watershed territories, collapses and transient ischaemic attacks or episodic movements associated with an orthostatic component. While positron emission tomography is the gold standard investigation for misery perfusion, advanced MRI is being increasingly used as an alternative investigation modality. The presence of CMP increases the risk of strokes. In addition to the devastating effect of stroke, there is accumulating evidence of impaired cognition and quality of life with carotid occlusive disease (COD) and misery perfusion. The evidence for revascularisation in the setting of complete carotid occlusion is weak. Medical management constitutes careful blood pressure management while addressing other vascular risk factors. Discussion The evidence for the management of patients with COD and CMP is discussed, together with recommendations based on our local experience. In this review, we focus on misery perfusion due to COD. Conclusion Patients with CMP and COD may present with a wide-ranging clinical phenotype and therefore to many specialties. Early identification of patients with misery perfusion may allow appropriate management and focus on strategies to maintain or improve cerebral blood flow, while avoiding potentially harmful treatment.